Advances in Reliability of Conducting Polymers and Conducting Polymer Based Capacitors in High Humidity Environment. (19th June 2018) - Chacko, Antony P; Jin, Yang; Shi, Yaru; Bunha, Ajaykumar; Chen, James; Lessner, Philip
Abstract : Polymer tantalum capacitors are emerging as an excellent choice for circuit designs that requires stable capacitance, long life, high reliability, and smaller size. Conductivity stability of Poly(3, 4-ethylenedioxythiophene) (PEDOT) materials as well as capacitors with PEDOT cathodes were investigated in this study. PEDOT films and cathodes formed from insitu polymerization of 3, 4-ethylenedioxythiophene monomer doped with p-toluenesulfonate (TOS) and pre-polymerized dispersion of PEDOT complexed with poly (styrene sulfonic acid) (PSSA) were compared under 85 °C/85% RH environment. Electrical measurements along with Raman Spectroscopy, X-ray Photoelectron Spectroscopy (XPS), UV Spectroscopy, Thermo-mechanical Analysis (TMA), and Thermal Imaging were used to characterize the samples. Resistance of the films formed from insitu polymerization increased significantly on exposure to 85 °C /85% RH compared to the films formed from pre-polymerized dispersion. However, the trend was reversed in the capacitors where cathodes formed by insitu polymerization was more stable than the cathodes from PEDOT: PSSA. Our studies suggest that delamination caused by the thermomechanical and voltage induced stress generated in these capacitors is primarily responsible for conductivity degradation in polymer capacitors. These new insights led to the development of a new generation of PEDOT: PSSA polymer systems which significantly enhanced the reliability of polymer capacitors in harsh environments.